THE EFFECT OF COMPETITIVE STRATEGIES ON PERFOMANCE OF PRIVATE PRIMARY SCHOOLS IN KENYA. A SURVEY OF PRIVATE PRIMARY SCHOOLS IN NAIROBI - NTHAMBI, JANE (African Journal of Education and Practice, 2016)
Purpose: The purpose of this study was to analyze the effect of competitive strategies on performance of private primary schools in Kenya. A survey of private primary schools in Nairobi Methodology: The research design for this study was explanatory research design. There are 350 private primary schools that are registered with Ministry of Education and also appear in the KNEC list. The study target population was 700 obtained from purposively targeting a Director and administrator from each school. A sample of 10% (70) was used. The researcher used Statistical Package for social Sciences (SPSS) to do the data analysis. Regression analysis was used to demonstrate the relationship between the competitive strategies and the performance of private schools in Nairobi County. Results: Cost leadership was found to affect level of performance in a positive manner. However, its effect was insignificant. Focus Competitive Strategies was found to positively affect level of performance. The relationship was positive and significant. Hence, employing focus strategies such as focusing on GCSE curriculum, focusing on students from the affluent class, focusing on students from middle class, international students and focusing on special subjects may improve school performance. It can be concluded that use of differentiations strategies such as offering GCSE curriculum, e-learning, research and development, extra-curriculum activities (music and arts) improve performance. Unique contribution to theory, practice and policy: T It is recommended that private primary schools should employ differentiation strategies as this would improve school performance. Schools should employ focus strategies such as focusing on GCSE curriculum, focusing on students from the affluent class, focusing on students from middle class, international students and focusing on special subjects as doing so may improve school performance